A Review of the Fairness of Inheritance Distribution for Boys and Girls in Islamic Law: A Gender Analysis - Agisna Fadilawati; Noorazmah Hidayati (al-Afkar, Journal For Islamic Studies, 2025)
The division of inheritance in Islamic law provides different shares between sons and daughters, where sons receive twice the share as daughters. However, this division is considered fair from an Islamic perspective, which views that justice does not always mean mathematical equality, but rather the granting of rights in accordance with the responsibilities and social roles of each individual. In Islamic society, men have a responsibility to provide for the family, so a larger share of inheritance is considered part of their economic responsibility. In contrast, women do not have the same obligations, and therefore, they are given a smaller but sufficient inheritance share to meet their personal needs. This article aims to analyze the principles of justice in the distribution of inheritance according to Islamic law, with a focus on differences in inheritance rights between boys and girls using library research research methods. This discussion will also examine the gender perspective in the distribution of inheritance, by criticizing what this system is. is still relevant to the concept of gender equality developing in modern society. The results of the analysis show that even though this distribution is unequal in number, the principles of Islamic justice still apply by providing rights in accordance with the social and economic obligations of each gender. In the modern context, some contemporary thinkers propose a reinterpretation to create a better balance between social justice and gender equality.